The Influence of the Jigsaw Learning Model on the Speaking Skills of Class V Students Theme 3 Maintaining Human Respiratory Organs at SDN 122390 Pematang Siantar - Rivaldo Sihombing; Eva Pasaribu; Napitupulu, Rio Parsaoran (Indonesian Journal of Advanced Research, 2023)
The aim of this research is to see the effect of Jigsaw learning on the speaking skills of class V students on theme 3 Maintaining Human Respiratory Organs at SDN 122390 Pematang Siantar. This type of research uses experimental research methods, which is a quantitative research method. This research design uses Pre-Experimental Design, where the research design is not yet a true experiment, because there are external variables that influence the shape of the dependent variable. The results of the research showed that students' speaking skills obtained an average pretest score of 58.91, whereas after being given treatment using the Inquiry model, an average posttest score of 81.30 was obtained and there was a significant influence of using the Jigsaw Type Cooperative learning model on student learning outcomes. It is known that the significance value (2-tailed) is 0.000. Then 0.000 < 0.05. This can be concluded to mean that Ho is rejected and Ha is accepted, which means that there is an influence of the Jigsaw cooperative learning model on the speaking skills of class V students, Sub Theme 3 Maintaining the Health of Human Respiratory Organs at SD N 122390 Pematangsiantar.